2022
DOI: 10.1002/anie.202205453
|View full text |Cite
|
Sign up to set email alerts
|

2D MOF with Compact Catalytic Sites for the One‐pot Synthesis of 2,5‐Dimethylfuran from Saccharides via Tandem Catalysis

Abstract: One pot synthesis of 2,5‐dimethylfuran (2,5‐DMF) from saccharides under mild conditions is of importance for the production of biofuel and fine chemicals. However, the synthesis requires a multitude of active sites and suffers from slow kinetics due to poor diffusion in most composite catalysts. Herein, a metal‐acid functionalized 2D metal‐organic framework (MOF; Pd/NUS‐SO3H), as an ultrathin nanosheet of 3–4 nm with Lewis acid, Brønsted acid, and metal active sites, was prepared based on the diazo method for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 80 publications
(15 reference statements)
0
35
0
Order By: Relevance
“…Two-dimensional (2D) MOFs with thicknesses of a few nanometers are novel materials with highly exposed active sites and weak resistance to the diffusion of reactants that have been widely investigated for use in various fields, including gas separation, catalysis, energy storage, electronic sensors, and biomedicine. [20][21][22][23][24][25][26][27] In the field of catalysis, metal-catalyzed redox reactions over 2D MOFs have been widely reported, such as oxidation of thioethers, oxidation of glucose, hydrogenation of nitroarene, hydrogenation of levulinic acid, and hydrosilylation of terminal olefins. [28][29][30][31][32][33] However, due to design limitations for localizing SO 3 H groups on 2D MOFs, few studies have been performed on acid-catalyzed applications of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) MOFs with thicknesses of a few nanometers are novel materials with highly exposed active sites and weak resistance to the diffusion of reactants that have been widely investigated for use in various fields, including gas separation, catalysis, energy storage, electronic sensors, and biomedicine. [20][21][22][23][24][25][26][27] In the field of catalysis, metal-catalyzed redox reactions over 2D MOFs have been widely reported, such as oxidation of thioethers, oxidation of glucose, hydrogenation of nitroarene, hydrogenation of levulinic acid, and hydrosilylation of terminal olefins. [28][29][30][31][32][33] However, due to design limitations for localizing SO 3 H groups on 2D MOFs, few studies have been performed on acid-catalyzed applications of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…This method usually refers to the adjustment of some material intermediaries in the synthesis process, such as the concentration and ratio of the reaction solvent or the pressure of the gas during the synthesis process, and finally obtaining the optimal size and structure of the material. [58][59][60] As a widely used material in recent years, the original shape and size of MOF can no longer meet the needs of today's applications. [61,62] Researchers have found that the method has a high success rate and has been extensively investigated.…”
Section: Controlled Mediation Methodsmentioning
confidence: 99%
“…19 For example, H 3 PW 4 O 12 , H 5 PMo 12 O 40 , H 5 PVMo 10 O 40 , H 5 PV 2 Mo 10 O 40 , and H 5 PV 3 Mo 10 O 40 acting as a Brønsted acid in POM@Cu-BTC composites have shown high efficiencies in dehydration reactions. 20,21 Since the dehydration reaction is an important step in the synthesis of PX following the cycloaddition reaction, inducing a POM into the MOF would be beneficial for constructing catalysts for PX synthesis. Furthermore, metal-catalyzed decarboxylative coupling has emerged as an efficient route to activate organic carboxylic acid that is involved in C–C coupling reactions at low temperatures.…”
Section: Introductionmentioning
confidence: 99%